2022
DOI: 10.3389/fpsyg.2021.794531
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Open Innovation Based on Mergers and Acquisitions on Innovative Behavior of Enterprises: Evidence From Chinese Listed Enterprises

Abstract: Finding the factors driving enterprise innovation behavior from multiple dimensions is of great significance for promoting enterprise innovation. Open innovation based on overseas mergers and acquisitions (M&A) has become one of the main ways for enterprises to obtain knowledge and technology. However, there is still no agreement on whether open innovation based on overseas M&A can promote innovation behavior of enterprises. Based on data from M&A transaction and enterprise patent of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For the measurement of service innovation behavior, refer to the scale [ 7 ] prepared by Scott and Bruce, which contains 4 items: “I am good at searching for new technologies, processes, technologies /product ideas in my work”. “In my work, I will generate creative ideas”; “I will investigate and seek the funds needed to implement new ideas”; “I will make appropriate plans and timetables for implementing new ideas”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the measurement of service innovation behavior, refer to the scale [ 7 ] prepared by Scott and Bruce, which contains 4 items: “I am good at searching for new technologies, processes, technologies /product ideas in my work”. “In my work, I will generate creative ideas”; “I will investigate and seek the funds needed to implement new ideas”; “I will make appropriate plans and timetables for implementing new ideas”.…”
Section: Methodsmentioning
confidence: 99%
“…Research on employee service innovation behavior is one of the hot spots in the field of human resource management. In the process of providing services, employees generate new ideas to solve problems and put them into practice, thus promoting organizational innovation, which plays an important role in promoting the core competitiveness of enterprises [ 7 ]. How to stimulate the service innovation behavior of the individual in the enterprise is always an important proposition in the organization management, but in some cases, even with the encouragement and promotion of the organization, many employees are still reluctant to experiment with service innovation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhou, Lingling, et al [39] found that green M&A improves operational efficiency and strengthens firms' development capacity. Wu et al [41] found that M&A can significantly promote innovation performance and innovation investment. Hu et al [43] consider the strengths of M&A arising from access to valuable resources, increased market share, profitability potential, and improvement of companies' long-term development capacities.…”
mentioning
confidence: 99%